Analysis of microscopic data under heterogeneous traffic conditions - Chunchu, Mallikarjuna; Kalaga, Ramachandra R.; Seethepalli, Naga V. S. K. (Transport, 2010)
Collecting microscopic data is difficult under heterogeneous traffic conditions. This data is essential when modelling heterogeneous traffic at a microscopic level. In this paper, microscopic data collected under heterogeneous traffic conditions using a video image processing technique is presented. Data related to heterogeneous traffic such as vehicle composition in the traffic stream, a lateral distribution of vehicles, lateral gaps and longitudinal gaps have been collected. The lateral distribution of vehicles on a ten‐meter wide road has been analyzed with a specific emphasis on motorized two‐wheeler movement. Using trajectory data, an attempt to examine the gap maintaining the behaviour of vehicles under different traffic conditions has been made. Empirical relationships between the lateral gap and area occupancy have been proposed for various vehicle combinations. The influence of difference in the lateral positions of leading and following vehicles on the longitudinal gap has been analyzed.First published online: 10 Feb 2011